(untitled) (Global Journal of Medical Research, 2015)
Two diagnostic methods, a modified Kinyoun’s acid-fast staining technique and an enzyme-linked immunosorbent assay (ELISA), for the detection of Cryptosporidium spp. in porcine faeces were compared regarding their sensitivities. Of the 209 faecal samples examined, Cryptosporidium spp. was detected significantly higher (p